Impaired Meningeal Lymphatic Flow in NMOSD Patients With Acute Attack - Wang, Xinxin; Tian, Haiyan; Liu, Han; Liang, Dongxiao; Qin, Chi; Zhu, Qingyong; Meng, Lin; Fu, Yu; Xu, Shuqin; Zhai, Yanping; Ding, Xuebing; Wang, Xuejing (Frontiers in Immunology, 2021)
The meningeal lymphatic vessels (mLVs) in central nervous system (CNS) has been validated by rodent and human studies. The mLVs play a vital role in draining soluble molecules and trafficking lymphocytes, antigens and antibodies from CNS into cervical lymph nodes (CLNs). This indicates that mLVs may serve as a link between the CNS and peripheral immune system, perhaps involving in the neuroinflammatory disease. However, the morphology and drainage function of mLVs in patients with neuroinflammatory disease, such as neuromyelitis optica spectrum disorders (NMOSD), remains unexplored. Using the dynamic contrast enhanced magnetic resonance imaging (DCE-MRI), we found that slower flow through mLVs along superior sagittal sinus in NMOSD patients with acute attack instead of NMOSD patients in chronic phase. The reduced flow in mLVs correlated with the disease severity evaluated by expanded disability status scale (EDSS). The receiver operating characteristic curve (ROC) indicated DCE-MRI might provide objective evidence to predict the acute relapse of NMOSD through evaluating the function of mLVs. Promoting or restoring the function of mLVs might be a new target for the treatment of NMOSD relapse.